PREDICTION STRATEGI BISNIS PADA KINERJA PERUSAHAAN SKALA KECIL MENENGAH MASA COVID-19 - Desfitrina; Zulfadhli; Triana Agustini (ILIN Institute, 2021)
Changes in people's behavior that reduce outdoor activities and networks of creative industries and small and medium-sized businesses in the largest business sector in the world that appear to be Covid-19 are quite depressed in dealing with problems and building businesses. The purpose of this study was to determine the effect of business strategy on the performance of small and medium-sized companies during the Covid-19 period. This research method is descriptive and verification methods, the analysis tool is structural equation modeling (SEM, Lisrel). The results show that how the influence of business strategy on the performance of small and medium scale companies during the Covid-19 period.